Exploring the potential of sensing nutrient dynamics using soil-based microbial fuel cells - Rekhi, Manjot Kaur (Kansas State University, 2022)
A soil-based microbial fuel cell (MFC) is a bio-electric device that uses soil microorganisms to convert an organic substrate into electricity. The energy generation potential of MFCs may be exploited to ‘sense’ the nutrient status of agricultural soils, which would be faster than traditional soil sampling methods and analysis in laboratories. It could provide real-time data on available soil nutrients. Our studies focused on developing a soil-based MFC that tracks changes in nutrient availability and explores relationships between soil nutrient availability, microbial activity, and MFC performance. We hypothesized that 1) a change in the level of nutrients would produce a different microbial response; hence, a different electrical signal and 2) introducing a biofilm coating on the anode would enhance electrogenic microbial activity and its ability to capture changes in nitrogen dynamics and voltage. A total of five different studies with two soils were conducted sequentially to test these hypotheses. Soil-based MFCs were set up with natural, partially sterilized (a treatment in study 1), and sterilized (a treatment in study 2) soil at field capacity with nitrogen fertilizer (studies 1, 3, 4, and 5), organic carbon treatments (study 2), and Geobacter enriched inoculum (study 4) and pre-developed Geobacter anodic coating (study 5). Soil 1 was used for studies 1-3, while soil 2 was used for studies 4 and 5. The voltage generated was measured by a data logger and recorded every 15 minutes. Soil solution was analyzed to estimate NO3-, NO2- and NH4+, dissolved organic carbon, pH, and electrical conductivity. Soil gas samples (CO2) were collected periodically as a proxy for soil microbial activity and soil organic carbon mineralization. The first study found that MFC performance was better in the control treatment than in higher nitrogen treatments. Voltage in higher nitrogen treatments was significantly low owing to possible nitrate reduction reactions using up the electrons, which could be used for voltage production, or the negative effect of N addition on organic matter decomposition. The voltage of the sterilized treatment decreased significantly with increasing dissolved nitrogen levels. The second study showed that different organic carbon treatments did not differ significantly in voltage, most likely due to non-significant changes in dissolved organic carbon caused by the organic carbon treatments. However, the voltage of sterilized treatment was significantly low, suggesting that the voltages produced in the other treatments were a result of various biotic processes. Biofilm on anode with different nitrogen levels performed better than the control soil. Voltage generation (or MFC performance) was higher with higher nitrogen levels than the control in the second soil. Differences in voltage signals with nitrogen levels were observed, but they varied by soil type, nutrient content, and presence of biofilm. Future studies plan to use a hydrogel-based anode coating to protect the anodic biofilm from exogenous soil microorganisms and selective inoculum of microorganisms for the nutrient in question. Although results are encouraging, more work is needed to deconvolute other signals from the voltage signal corresponding to available soil N levels. If we can successfully model these relationships, this research could help improve crop production rates and ensure the Nation’s food security through 2050 demands.
Keywords: Soil microbial fuel cell; Biosensor; Soil nitrate dynamics; Microbial organic carbon oxidation; Facultative nitrate reduction